Soybean Proteome Database 2012: update on the comprehensive data repository for soybean proteomics - Ohyanagi, Hajime; Sakata, Katsumi; Komatsu, Setsuko (Frontiers in Plant Science, 2012)
The Soybean Proteome Database (SPD) was created to provide a data repository for functional analyses of soybean responses to flooding stress, thought to be a major constraint for establishment and production of this plant. Since the last publication of the SPD, we thoroughly enhanced the contents of database, particularly protein samples and their annotations from several organelles. The current release contains 23 reference maps of soybean (Glycine max cv. Enrei) proteins collected from several organs, tissues and organelles including the maps for plasma membrane, cell wall, chloroplast and mitochondrion, which were electrophoresed on two-dimensional polyacrylamide gels. Furthermore, the proteins analyzed with gel-free proteomics technique have been added and available online. In addition to protein fluctuations under flooding, those of salt and drought stress have been included in the current release. An omics table also has been provided to reveal relationships among mRNAs, proteins and metabolites with a unified temporal-profile tag in order to facilitate retrieval of the data based on the temporal profiles. An intuitive user interface based on dynamic HTML enables users to browse the network as well as the profiles of multiple omes in an integrated fashion. The SPD is available at: http://proteome.dc.affrc.go.jp/Soybean/.